The principal's role in improving the quality: A concepts framework to developing school culture - Sumiran, Sumiran; Waston, Waston; Zamroni, Zamroni; Mahmudah, Fitri Nur (Frontiers in Education, 2022)
This study aims to explore the role of principals in school culture so as to produce an ideal conceptual framework for principals in improving school quality. The method used in this research is qualitative with a case study approach. The research was conducted in MAN 2 Sragen and MAN 2 Boyolali, Indonesia. The data analysis procedure used is Miles & Huberman with four procedures. Data analysis was carried out with the help of Atlas.ti software version 8. Validity was carried out using data triangulation. The results of this study illustrate that the principal's role in school culture to improve school quality consists of role sets, attitudes and actions, personality characteristics, and control. This research recommendation is intended by principals at any level, both primary and secondary levels, to be able to pay attention to important points from research results in order to improve school quality and create certain characteristics that are unique and superior characteristics compared to other schools.